2019
DOI: 10.1152/ajplung.00264.2018
|View full text |Cite
|
Sign up to set email alerts
|

Role of dual-specificity protein phosphatase DUSP10/MKP-5 in pulmonary fibrosis

Abstract: Mitogen-activated protein kinase (MAPK) phosphatase 5 (MKP-5) is a member of the dual-specificity family of protein tyrosine phosphatases that negatively regulates p38 MAPK and the JNK. MKP-5-deficient mice exhibit improved muscle repair and reduced fibrosis in an animal model of muscular dystrophy. Here, we asked whether the effects of MKP-5 on muscle fibrosis extend to other tissues. Using a bleomycin-induced model of pulmonary fibrosis, we found that MKP-5-deficient mice were protected from the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…We also demonstrated that mice lacking MKP-5 are resistant to pulmonary fibrosis in response to bleomycin-induced lung injury (27). Mechanistically, these studies indicated that MKP-5 may positively regulate TGF-b1 signaling, which is an underlying mechanism for pathological fibrogenesis (23,27). However, the role of MKP-5 in pathological myocardial fibrosis has yet to be determined.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…We also demonstrated that mice lacking MKP-5 are resistant to pulmonary fibrosis in response to bleomycin-induced lung injury (27). Mechanistically, these studies indicated that MKP-5 may positively regulate TGF-b1 signaling, which is an underlying mechanism for pathological fibrogenesis (23,27). However, the role of MKP-5 in pathological myocardial fibrosis has yet to be determined.…”
Section: Introductionmentioning
confidence: 82%
“…Specifically, we have demonstrated that MKP-5 deficiency exerts a protective effect on the progression of muscular dystrophy, including the development of fibrosis in skeletal muscles (23). We also demonstrated that mice lacking MKP-5 are resistant to pulmonary fibrosis in response to bleomycin-induced lung injury (27). Mechanistically, these studies indicated that MKP-5 may positively regulate TGF-b1 signaling, which is an underlying mechanism for pathological fibrogenesis (23,27).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, mice with a systemic deletion of Dusp10 , which is an equipotent phosphatase of JNK and p38 (also known as MKP-5), show clear resistance to BLM-induced lung fibrosis [ 109 ]. In this situation, macrophages were markedly polarized to the M1 phenotype.…”
Section: Involvement Of P38 In the Pathogenesis Of Pulmonary Fibrosismentioning
confidence: 99%
“…There has been renewed interest in molecules such as members of the cellular communication network (CCN) ( 12 ) and the insulin-like growth factor (IGF) ( 3 , 22 ) family of proteins and their functions in the setting of lung fibrosis. Moonlighting functions for enzymes such as sialidases ( 11 ) and phosphatases ( 1 , 18 , 21 ) have been identified. Research into mechanisms mediating oxidative stress and its role in lung fibrosis has continued ( 6 ).…”
mentioning
confidence: 99%